The Influence of Type 1 Diabetes Mellitus on Dental Caries and Salivary Composition - Lulëjeta Ferizi; Fatmir Dragidella; Lidvana Spahiu; Agim Begzati; Vjosa Kotori (Hindawi Limited, 2018)
Diabetes mellitus is the most common chronic disease that affects the oral health. The aim of the study is to evaluate the dental caries, salivary flow rate, buffer capacity, and Lactobacilli in saliva in children with type 1 diabetes mellitus compared to the control group. Methods. The sample consisted of 160 children of 10 to 15 years divided into two groups: 80 children with type 1 diabetes mellitus and 80 children as a control group. Dental caries was assessed using the DMFT index for permanent dentition. Stimulated saliva was collected among all children. Salivary flow rate and buffer capacity were measured, and the colonies of Lactobacillus in saliva were determined. The observed children have answered a number of questions related to their dental visits and parents' education. The data obtained from each group were compared statistically using the chi-square test and Mann-Whitney U-test. The significant level was set at p<0.05. Results. DMFT in children with type 1 diabetes was significantly higher than that in the control group (p<0.001). Diabetic children have a low level of stimulated salivary flow rate compared to control children (0.86 ± 0.16 and 1.10 ± 0.14). The buffer capacity showed statistically significant differences between children with type 1 diabetes and control group (p<0.001). Also, children with type 1 diabetes had a higher count and a higher risk of Lactobacillus compared to the control group (p<0.05 and p<0.001). Conclusion. The findings we obtained showed that type 1 diabetes mellitus has an important part in children's oral health. It appears that children with type 1 diabetes are exposed to a higher risk for caries and oral health than nondiabetic children.